Kemampuan Literasi Matematika Siswa dalam Menyelesaikan Soal Matematika Terintegrasi Islam - Rizqiya Hasanah; M. Imamuddin; Isnaniah; Herlina Yulia Kumalasari (JUMAT: Jurnal Matematika, 2024)
Literacy skills and Islamic values must be possessed by every student. This must also occur in mathematics learning. This study aims to analyze students' mathematical literacy skills in solving Islamic integrated mathematics problems. This type of research uses qualitative research with the aim of describing phenomena in depth. This research was conducted at MTsN 3 Agam at 2023/2024. The sample was 30 students from classes VII and VIII. Data collection was done with tests and interviews. The tests given were in the form of mathematical literacy questions with indicators of communication at the level of applying (C3) and representation at the level of analyzing (C4). Interviews were conducted in depth related to student work after working on test questions so that information could be obtained related to the difficulties or obstacles faced by students while solving Islamic integrated mathematics literacy problems. The results showed that from the test results conducted by students, the average category of assessment of student test results was 3% very good category, 33% good enough category, and 64% poor category. From this percentage, it shows that mathematical literacy skills in MTsN 3 Agam students are still low so that it is necessary to improve mathematical literacy skills in MTsN 3 Agam students.